Hospital Location Selection with Grey System Theory - Şen, Halil; Demiral, Mehmet Fatih (European Journal of Economics and Business Studies, 2016)
The facility location selection is one of the most important decisions for investors and entrepreneurs. It is a strategic issue besides often decides the fate of such a facility. In this kind of strategic decisions, decision makers should take into account various objectives and criteria and the process of location selection is inherently complicated. This paper considers the hospital location selection for a new public hospital by using Gray Relational Analysis (GRA) and Analytic Hierarchy Process (AHP). Gray Relational Analysis have been developed based on Grey System Theory. Grey System Theory is an interdisciplinary approach which first quantified by Deng in the early 1980’s as an alternative method in creating the uncertainty have been proposed. The basic idea of emergence is to estimate the behavior of the systems which cannot be overcome by the stochastic or fuzzy methods with limited number of data. In this paper, the weights of criteria have been determined by using Analytic Hierarchic Process, then the grey relational degrees have been calculated for each alternative location.